A modified technique for nipple-areola complex reconstruction - Shoeib A. Mohamed; Peir Camillo Parodi (Indian Journal of Plastic Surgery)
Background: From a historical perspective, many techniques of nipple reconstruction have been performed, including a graft from the contralateral nipple, composite grafts such as toe pulp or earlobe tissue and even an intra-dermal tattoo alone. This is the final stage of breast reconstruction, and is carried out only when the surgeon is confident that acceptable symmetry and shape of the reconstructed breast has been achieved. The technical challenges of nipple reconstruction include correcting position, maintaining adequate projection and creating an inconspicuous scar. An alternative to a surgically reconstructed nipple is the use of silicone prosthetic nipples. Materials and Methods: From August 2006 until September 2007, 80 cases of nipple/areola reconstruction were performed in our department (UDINE UNIV.) following mammary reconstruction or conservative breast surgery. Forty cases were carried out with the classical technique and another 40 cases with the introduction of our modification in the form of deepithelization of a semicircular area of the adjacent skin at the base of the flap. Postoperative follow-up as regards the nipple size, site, projection, symmetry and donnar scar were assessed. Patient satisfaction was also addressed and evaluated. Results: There were good to excellent results as regards nipple size, symmetry and projection. The technique is suitable for different autologous and implant reconstruction. The technique is an outpatient procedure, is easy and is not consuming time. Areolar graft from the contra-lateral areola is colouur matching and shows nearly no deference from the opposite one. Conclusions: Simple technique and not time consuming. Maintains the consistency and projection of the new nipple. Patient satisfaction. Minimal complication.